2014
DOI: 10.1007/s10151-014-1168-2
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating injury to the buttock: an update

Abstract: Clinical research on penetrating injury to the buttock is sparse and largely limited to case reports and clinical series. The purpose of this paper is to provide a detailed overview of literature of the topic and to propose a basic algorithm for management of penetrating gluteal injuries (PGI). MEDLINE, EMBASE, Cochran, and CINAHL databases were employed. Thirty-seven papers were selected and retrieved for overview from 1,021 records. PGI accounts for 2-3 % of all penetrating injuries, with a mortality rate up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 50 publications
0
21
1
Order By: Relevance
“…Those relevant to our case are first, external bleeding from a wound initially treated conservatively with a deeper injury difficult to assess surgically and second, a pseudoaneurysm 16. In our case, given the presence of a small pseudoaneurysm on initial CT imaging, a digital subtraction angiogram may have allowed embolisation of the pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Those relevant to our case are first, external bleeding from a wound initially treated conservatively with a deeper injury difficult to assess surgically and second, a pseudoaneurysm 16. In our case, given the presence of a small pseudoaneurysm on initial CT imaging, a digital subtraction angiogram may have allowed embolisation of the pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 89%
“…One recent review synthesised the sparse evidence to devise a management algorithm for penetrating gluteal injuries 16. It is suggested that patients in hypovolaemic shock should progress directly to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery, angioembolization or observation could be preferred according to the observed bleeding and abdominal injuries. 2 In 2014, Lunevicius et al, 8 updated the algorithm and recommended evaluation in the following order: general inspection of the patient, controlling the femoral pulse, neurological examination of the lower extremities, examination of urethra and rectum, and then rectoscopy was suggested after the patient became stable. 9 Radiologists recommend contrast-enhanced rectal CT if there is still clinical suspicion of rectal injury despite rectoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…There is no generally accepted method for evaluating gluteal region penetrating injuries. However, a new algorithm was introduced by Lunevicius et al (6) Control of the femoral pulse and the external urethral meatus, neurological examination of the lower extremities, and examination of the rectum should definitely be performed after general inspection according to this algorithm. If there are shock findings in the patient, damage control surgery or definitive surgery should quickly be performed.…”
Section: Discussionmentioning
confidence: 99%
“…If the patient is stable, examination should be continued. In the case of clinical suspicion, rectoscopy/rectosigmoidoscopy should be planned (6). If the bleeding through the skin cannot be brought under control by tamponade, arteriography (Doppler ultrasonography, CT angiography, or invasive angiography) should be planned (7).…”
Section: Discussionmentioning
confidence: 99%